Unveiling the fungal frontier: mycological insights into inflammatory bowel disease - Chen, Silan; Yi, Meijing; Yi, Xinying; Zhou, Yuxuan; Song, Houpan; Zeng, Meiyan (Frontiers in Immunology, 2025)
Inflammatory bowel disease (IBD) is a chronic recurrent gastrointestinal disease that seriously affects the quality of life of patients around the world. It is characterized by recurrent abdominal pain, diarrhea, and mucous bloody stools. There is an urgent need for more accurate diagnosis and effective treatment of IBD. Accumulated evidence suggests that gut microbiota plays an important role in the occurrence and development of gut inflammation. However, most studies on the role of gut microbiota in IBD have focused on bacteria, while fungal microorganisms have been neglected. Fungal dysbiosis can activate the host protective immune pathway related to the integrity of the epithelial barrier and release a variety of pro-inflammatory cytokines to trigger the inflammatory response. Dectin-1, CARD9, and IL-17 signaling pathways may be immune drivers of fungal dysbacteriosis in the development of IBD. In addition, fungal-bacterial interactions and fungal-derived metabolites also play an important role. Based on this information, we explored new strategies for IBD treatment targeting the intestinal fungal group and its metabolites, such as fungal probiotics, antifungal drugs, diet therapy, and fecal microbiota transplantation (FMT). This review aims to summarize the fungal dysbiosis and pathogenesis of IBD, and provide new insights and directions for further research in this emerging field.